Microbial biomass nitrogen in soil cultivated with soybean, under different management systems, in the Cerrado - Perez, Kátia Sueli Sivek; Ramos, Maria Lucrecia Gerosa; McManus, Concepta (Pesquisa Agropecuaria Brasileira, 2005)
The aim of this work was to quantify soil nitrogen microbial biomassa (SNMB) under different soil management systems: no-tillage (NT); one harrowing (OH); one subsoiling with two harrowings (SH). These systems were compared with native Cerrado, on a Red Yellow Latossol clay, in Federal District. Soils were studied at five depths, 0–5, 5–10, 10–20, 20–30 and 30–40 cm, over four periods: before soil preparation; 30 days after germination (DAG); flowering stage and after harvesting soybean plants. The native Cerrado showed the highest values of SNMB in all periods and management systems. Significant differences were found between 0–5, 5–10 and 10–20 cm soil layers, except at 30 DAG. The Nmic:Ntotal percentual ratio in cerrado soil was 2.5 times greater than OH system, three times greater than NT and five times greater than SH. The distribution of total N decreased in the Cerrado soil and other management systems with soil depth. Total N levels decreased with soil depth in all periods. There was a positive correlation between nutrients and microbial nitrogen in different management systems and soils under native cerrado vegetation.